Effectiveness of Ease of Use of Google Forms in Improving the Efficiency of Ordering Data Management and User Satisfaction at the Faculty of Economics and Business, State University of Jakarta - Permana, Azzahra Nazwa Nabila; Hidayah, Fathul; Usman, Osly (International Conference on Digital Business Innovation and Technology Management (ICONBIT), 2025)
Abstract. This study aims to analyze the Effectiveness of Google Form in Improving the Efficiency of Danusan Order Data Management at State University of Jakarta. The research method used is quantitative with a survey approach, where data is collected through questionnaires distributed to students involved in purchasing transactions. The use of Google Form also increases transparency in the buying and selling of danusan goods, because all data is recorded automatically and can be accessed easily. This contributes to the reduction of potential losses due to recording errors, as well as improving the buyer’s experiesnce in conducting transactions. Overall, this research shows that the implementation of Google Forms in the ordering system of danusan goods at State University of Jakarta not only improves time and transaction efficiency, but also provides an innovative solution that can be applied on other campuses to improve effectiveness and transparency in fundraising management.